2020
DOI: 10.1186/s13002-020-00384-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotany of dye plants in Southern Italy, Mediterranean Basin: floristic catalog and two centuries of analysis of traditional botanical knowledge heritage

Abstract: Background: Since ancient times, man has learned to use plants to obtain natural dyes, but this traditional botanical knowledge (TBK) is eroding. In the late, during, and the early 1800s, there was an increase in research related to dye species, and this allowed the development of industry and economy in rural contexts of Southern Italy. Today, dyes are mainly obtained from synthetic products, and this leads to risks for human health related to pollution. Methods: Starting from the literature, three catalogs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…These last ones, given their diffusion in Sicily, define territorial mosaics with a high "widespread naturalness" [61], in which extensive agricultural practices are applied with a low environmental impact, compatible with the sustainable management of natural resources. They host rather diversified residual habitats, characterized by species of high conservation interest (e.g., [62][63][64][65][66][67]) and by a rich flora of ethnobotanical interest that is used for food purposes by local populations [68,69] or for its dyeing properties [70]. Along the margins, there are frequent residues of the ancient Rhus coriaria L. cultivation, recently re-evaluated for the antioxidant properties of the fruits [71].…”
Section: Discussionmentioning
confidence: 99%
“…These last ones, given their diffusion in Sicily, define territorial mosaics with a high "widespread naturalness" [61], in which extensive agricultural practices are applied with a low environmental impact, compatible with the sustainable management of natural resources. They host rather diversified residual habitats, characterized by species of high conservation interest (e.g., [62][63][64][65][66][67]) and by a rich flora of ethnobotanical interest that is used for food purposes by local populations [68,69] or for its dyeing properties [70]. Along the margins, there are frequent residues of the ancient Rhus coriaria L. cultivation, recently re-evaluated for the antioxidant properties of the fruits [71].…”
Section: Discussionmentioning
confidence: 99%
“…In other works, interviewers reported that the leaves of Morus alba are better than the latter, especially if the silkworm is in the first phase of growth. This shows the importance of the plant when the art of silk production was a source of income for the household [97,98].…”
Section: Handcraft and Domestic Usesmentioning
confidence: 93%
“…ere are 95 families, 181 genera, 213 species of colored leaves, and 29 species of 16 families of colored flowers (Table 1). Exploration by Prigioniero et al [13] in Southern Italy, Mediterranean Basin, identified 64.31% of plant species producing colors that were 25.2% of leaves and 18.5% of flowers.…”
Section: Resultsmentioning
confidence: 99%